El papel de la Mujer en la Iglesia Católica de América Latina - Marín, Vania (SocietàMutamentoPolitica, 2018)
This article is a reflection on the role and participation of women in the Latin American Catholic Church. For this it proceeds in three stages. In the first place, it presents the position of the Latin American Catholic Church regarding the condition and participation of women in the ecclesial sphere. He then analyzes the various feminist movements in Latin America and their impact on society and the Latin American Church. Finally, he analyzes Latin American feminist theology as a form of radical rupture with the patriarchal practices of society and the Church in Latin America.